Efektivitas Modul Hybrid Project Based Learning (H-Pjbl) Berbasis Laboratorium Untuk Meningkatkan Keterampilan Proses Sains Siswa - Ihsan Nurdiansah; Yanti Sofi Makiyah (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
This study aimed to described the effectiveness of the Laboratory-Based Hybrid Project Based Learning Module to improve students' science process skills. This study uses a quasi-experimental method with a one-group pre-test pre-test design. The research sample was selected randomly from the population of class X TKRO SMKN 1 Manonjaya students. Data analysis was seen from the results of the pre-test pre-test obtained by students, t-test and N-gain to determine the improvement of students' scientific process skills descriptively. The results of the study obtained that the results of the pre-test and post-test of students increased by 37.26%, then the t-test analysis where t_count > t_table obtained a value of 3.54> 1.76 then Ho was rejected so that there was a significant difference between the pretest and posttest scores. after using the laboratory-based Hybrid Project Based Learning module, it can improve students' science process skills (KPS). However, based on the gain value obtained, 0.3 is still categorized as "medium" because there are several shortcomings during the teaching and learning process (KBM).